50 joined Post Flood Volunteer Mission in Mentakab - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
MENTAKAB, 26 December 2021 - Sludge and muddy water were like an ocean of ‘teh tarik’ in several flood locations in Mentakab.